Traction behavior of soccer shoe stud designs under different game-relevant loading conditions - Grund, T.; Senner, V. (Procedia Engineering, 2010)
Testing soccer shoes with appropriate tests and under loading situations that are as realistic as possible are requirements to get close insight into the shoe-surface interaction of studded shoes on turf. Therefore a new test device was developed and optimized. Four soccer shoes with different stud designs were tested on natural grass under four different loading patterns estimated from real ACL-injury situations and the torque around the tibial axis was measured. Differences between the shoes could be detected during all loading patterns. In contrast to earlier studies we found that aggressively cleated shoes did not generate higher torque than conventionally cleated shoes.